INCLUSION LEARNING MODEL; MENGATASI KESULITAN BELAJAR SISWA DALAM SPECIFIC LANGUAGE IMPAIRMENT - Fathor Rozi; Hoiron Nisa’ (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
The purpose of this study was to find out how the implementation of the inclusive learning model to overcome the learning difficulties of students with specific language impairment characteristics. This research was conducted at MI Nurul Islam Kalibuntu Kraksaan Probolinggo with a qualitative approach through case study research. The data were obtained from the observation process, interviews with the Madrasah Headmaster, class III teacher, one of the student's guardians, and one of the MI Nurul Islam students, and documentation. The process of data analysis by collecting data, reducing data, presenting data, and concluding data findings. The results show the success of applying the inclusive learning model to specific language impairment (SLI) students at MI Nurul Islam. This learning process was successful through storytelling activities, reading a book story, playing word chains, and threats with stimulation of random words. This inclusive learning model succeeded in overcoming the learning difficulties of class III students in aspects of SLI or language disorders. This inclusive learning model is able to provide stimulus and stimulation that is flexible to the needs of SLI students. This learning model is a good contribution to the sustainability of educational goals which require students to enrich literacy towards the future era of globalization.